Developing analytical tools for saccharides in condensed phases - Kuttel, Michelle Mary (Department of Chemistry, 2016)
Carbohydrates are conformationally very complex molecules. It is this complexity that lies at the basis of the important roles that these molecules play in many biochemical and biomaterial systems. Moreover, the unusual response of these macromolecules to their environment allow them to play these often critical roles. This is particularly true for solvated carbohydrates. A knowledge of the molecular structure of carbohydrates is essential for an understanding of their function and the molecular basis of their macroscopic properties. The details of solution structure have proven difficult to probe experimentally, but computer simulations are a means for examining solvent structure directly. In this thesis we develop various computational methods for analysing saccharides in solution and in the solid state. These methods are applied to molecular dynamics simulations of maltose, hexa-amylose and a series of cyclodextrins in solution, in order to investigate the effects of water on these polysaccharides. Maltose is investigated because of its potential as a model for larger polysaccharides comprising α(1 → 4)-linked glucose monomers. Solvation was found to effect the conformations of the saccharides studied considerably. In particular, the range of motion around the glycosidic linkage is increased. Comparison of the dynamics around the glycosidic linkages for the various simulation show that oligosaccharides linked via α(1 → 4) glycosidic linkages have similar behaviour around this linkage. The saccharides studied were found to impose considerable anisotropic structure on the surrounding water which may give insights into their solution properties. In addition to the studies in solution, a recently developed method for analysing the close contacts in crystal structures is applied to crystal structures of cyclodextrin inclusion compounds. It shown to be a useful tool for investigating hydrogen-bonding patterns in the cyclodextrins.